ULTRAFAST PAPANICOLAOU STAINING FOR CANINE VAGINAL EXFOLIATIVE CYTOLOGY - KULASEKAR, K; SRIDEVl, p; ARUNMOZHI, N; BALASUBRAMANIAN, S; SATHIAMOORTHY, T (The Indian Journal of Animal Reproduction, 2023)
Several Staining Technique have been used to evaluate vaginal cell morphology in bitches. The present study was done to evaluate papanicolaou staining to study the v· ginal exfoliative cytology in bitches. A total of 500 vaginal smears obtained from bitches presented to the small animal gynaecology unit of Madras Veterinary College Teaching Hospital were utilised for the study. 29.0, 51.8, 8.8 and 5.4, per cent were found to be in proestrus, estrus, di estrus and anestrus. The para basal, intermediate cells appeared blue and that of superficial and cornified cells pink in colour. This staining technique help to differentiate cell type based on colour rather than morphology which get altered during the collection of vaginal smears within a short time.